The pathology of oxidative stress-induced autophagy in a chronic rotator cuff enthesis tear - Prasetia, Renaldi; Purwana, Siti Zainab Bani; Lesmana, Ronny; Herman, Herry; Chernchujit, Bancha; Rasyid, Hermawan Nagar (Frontiers in Physiology, 2023)
Partial-thickness rotator cuff tears (PTRCTs) are often found in daily orthopedic practice, with most of the tears occurring in middle-aged patients. An anaerobic process and imbalanced oxygenation have been observed in PTRCTs, resulting in oxidative stress. Studies have shown the roles of oxidative stress in autophagy and the potential of unregulated mechanisms causing disturbance in soft tissue healing. This article aims to review literatures and to summarize the potential pathology of oxidative stress and unregulated autophagy in rotator cuff enthesis correlated with chronicity. We collected and reviewed the literature using appropriate keywords, in addition to manually retrieved literature. Autophagy is a normal mechanism of tissue repair or conversion to energy needed for the repair of rotator cuff tears. However, excessive mechanisms will degenerate the tendon, resulting in an abnormal state. Chronic overloading of the enthesis in PTRCTs and the hypovascular nature of the proximal tendon insertion will lead to hypoxia. The hypoxia state results in oxidative stress. An autophagy mechanism is induced in hypoxia via hypoxia-inducible factors (HIF) 1/Bcl-2 adenovirus E1B 19-kDa interacting protein (BNIP) 3, releasing beclin-1, and resulting in autophagy induction. ROS accumulation would induce autophagy as the regulator of cell oxidation. Oxidative stress will also remove mammalian target of rapamycin (mTOR) from the induction complex, causing phosphorylation, and initiating autophagy. Hypoxia and endoplasmic reticulum (ER) stress would initiate unfolded protein response (UPR) through protein kinase RNA-like ER kinase (PERK) and activating transcription factor (ATF) 4, which induces autophagy. Oxidative stress occurring in the hypovascularized chronic rotator cuff tear due to hypoxia and ROS accumulation would result in unregulated autophagy directly or autophagy mediated by HIF-1, mTOR, and UPR. These mechanisms would disrupt enthesis healing.